The Political Communication of the Regent of Garut in Enhancing Public Trust in Garut Regency - Renti Oktavianti; Meliasta Hapri Tarigan (Journal of Social and Policy Issues, 2026)
This study aims to determine the effectiveness of the Regent of Garut's political communication in enhancing public trust in the digital era. The research employs a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, then analyzed systematically through the stages of data reduction, data presentation, and conclusion drawing. The theoretical framework used is political communication theory, encompassing three main dimensions: political communicators, political messages, and political audiences. The findings indicate that the political communication of the Regent of Garut has utilized social media and direct communication to build closer relationships with the community. Communicator credibility, message clarity, and issue relevance are key factors in shaping public perception. However, a gap was found between the image constructed in digital media and the reality experienced by some members of the public, which has unevenly affected the level of public trust. This study concludes that effective political communication requires consistency between delivered messages and policy implementation, improved responsiveness to public aspirations, and optimized participatory two-way communication. Periodic evaluations of digital-based communication strategies are also necessary to ensure transparency, accountability, and alignment with community needs, in order to sustainably strengthen the legitimacy of regional leadership.